Analysis of landslide in chosica using satellite images - Roman Gonzalez, Avid (2017)
Early in the year, Peru suffered from heavy rains mainly due to the El Niño and La Niña phenomena. As a result of these heavy rains, several cities were affected by floods and landslides. One of the most affected cities was Chosica. On the other hand, the satellite images have many applications, one of them is the aid for a better management of the natural disasters (post-disaster management). In this sense, in the present work, one proposes the use of radar satellite images to make an analysis of the most-affected areas by landslides in the city of Chosica. The results show a significant number of places flooded according to satellite images of March 2017. The satellite images used were from the Sentinel 1 satellite belonging to the European Union.